Interpretation of Morphological Details of Nondegenerated Lumbar Intervertebral Discs on Magnetic Resonance Imaging: Insights From a Comparison Between Computed Tomography Discograms and Magnetic Resonance Imaging. Issue 3 (14th May 2022) - Sharma, Aseem; Lagerstrand, Kerstin; Brisby, Helena; Hebelka, Hanna
Abstract : Objective: To gain better insight into the magnetic resonance imaging (MRI) appearance of morphological intervertebral disc (IVD) details, such as annular and nucleus pulposus dimensions, by comparing contemporaneously obtained MRI and postdiscogram computed tomography (CT) scans of nondegenerated IVDs. Methods: Axial T2-weighted images and same-day postdiscography CTs, acquired after the MRI, of 26 normal-appearing lumbar IVDs (control IVDs at discography) were compared. The location and extent of central hyperintense zone on MRI and the extent of contrast distribution on CT relative to the IVD width (in anteroposterior [AP] and lateral planes) were assessed, with difference in measures between the modalities used to provide apparent inner annulus thickness and to estimate dimensions of also the outer annulus and location of nucleus pulposus. Results: The mean (SD) extent of contrast distribution on CT discograms (53.1% [6.6%] and 58.1% [8.7%] of AP and lateral IVD width) was smaller than ( P < 0.001 for both), and correlated weakly (r = 0.31 and 0.32 for AP and lateral planes) with corresponding measurements (58.4% [5.3%] and 65.7% [5.9%], respectively) for central hyperintense zone at MRI. The center of contrast opacification on CT discograms was located posterior to that of central T2 hyperintense zone on MRI in AP ( P < 0.01), without any difference in lateral direction ( P = 0.60). Conclusions: Normal-appearing lumbar IVDs are supported by outer annulus of larger relative thickness anteriorly, seen on both modalities. The shown discrepancy between the central T2 hyperintense zone and contrast distribution on CT discogram might reflect the inner annulus or structural changes within the borderzone nucleus and annulus. The exact nucleus size and inner annulus thickness could not be established due to a variable permeation of contrast across the central hyperintense zone on T2-weighted images.